PENGARUH KUALITAS PELAYANAN DAN FASILITAS TERHADAP KEPUASAN WISATAWAN NUSANTARA DI DAYA TARIK WISATA KEBUN RAYA “EKA KARYA” BALI - Angga Suputra Jayadi; I GPB. Sasrawan Mananda; Ni Made Oka Karini (Department of Tour and Travel Studies, Faculty of Tourism, Udayana University, 2022)
This study aims to determine the effect of service quality and facilities on the satisfaction of domestic tourists in the tourist attraction of the